Incumplimiento por parte del estado ecuatoriano en la rehabilitación integral de las personas privadas de la libertad para que accedan a su reinserción social con el cambio de régimen semiabierto - Agila Yaguache, José Miguel (2022)
The following research work entitled: "Failure by the Ecuadorian State in the Integral Rehabilitation of persons deprived of their freedom to access their social reinsertion through the Semi-Open Regime". This work has been created since the recent events in Ecuador have been vulnerable in the Rehabilitation system and its failure of rehabilitation within prisons. The study shows the lack of capacity on the part of the State to guarantee adequate rehabilitation and social reinsertion, since the Penitentiary System lacks an adequate structure to allow occupational careers, there are no adequate psychological orientation processes that allow these people to modify their criminal behavior. Moreover, the State does not have a moderate budget or economic allocation for this purpose, therefore this research seeks to find the causes that do not allow the Rehabilitation Centers to fulfill their true function. To carry out the present research, resources, materials and methods were applied, as well as interviews and surveys to legal professionals, whose results were used to propose the legal reform project to the Organic Integral Criminal Code and the regulations of the National System of Social Rehabilitation, in order to make the axes of treatment of persons deprived of liberty mandatory, as well as to establish those requirements that a person must have in order to hold the position of General Director of the National System of Social Rehabilitation.